METHOD OF GENERATING AND HOLDING Z-PINCH-TYPE PLASMA WITH INVERTED FIELD - TIKHIRO OKHKAVA,JP (1987)
A multipole plasma pinch method and apparatus produces hot magnetically confined z-pinch plasma with a plurality of z-pinch current channels arranged so as to generate a multipolar magnetic field and at least one hyperbolic magnetic axis within the plasma space roughly enclosed by the channels, forming thereby a region of average magnetic well in a region of nested closed plasma magnetic surfaces surrounding the plasma current channels, when the magnetic field component in the direction of the hyperbolic axis is also made to be substantially zero in the vicinity of the hyperbolic axis. The multipole pinch invention may be operated so that q and field reversal take place within the plasma, and the plasma so produced closely approximates known theoretical stability conditions. The well-producing hyperbolic axis of the present invention is produced effectively by replacing the solid conducting rings of prior art multipole plasma confinement devices by z-pinch-like toroidal current channel loops of plasma. The plasma is formed inside a vacuum chamber and an electrically conducting shaping shell assembly, whose noncircular poloidal cross section imparts the desired shape to the plasma. The shape of the plasma may be maintained and/or adjusted by means of electrical currents driven through appropriately distributed external conductors.